Analisis Teknik Permainan Keyboard dalam Mengiringi Nyanyian Rohani Methodist Indonesia No.20.Tolong Hamba-MU Ya Allah - Ayu Napitupulu; Roy JM Hutagalung; Diana M Situmeang (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
The aim of this research is to analyze the keyboard playing technique of Hymn No.20. Help YOUR servant, O Allah. The object of this research is focused on the analysis of keyboard playing techniques in the song NRM.no 20 Please Your Servant Ya Allah. This research uses a qualitative approach method. The subject of this research is the score for the song NRM no. 20 Please Your Servant Ya Allah. This research focuses on problems related to keyboard playing techniques in the song Please Servant-Mu Ya Allah. Data was obtained through data collection techniques such as observation, interviews and documentation. Data is analyzed by presenting data and drawing conclusions. In fact, the study in this thesis is based on the problems the author discusses. Then the results of the data produce conclusions which are the solution to the problem in this thesis. The results of this research show that the keyboard player's techniques found in the song iNRM no. 20 Please Your Servant Ya Allah are that there are keyboard playing techniques in this song using basic techniques such as correct hand positions, correct fingering techniques and dynamic techniques. By knowing keyboard playing techniques to make it easier for piano players to play the song MRM no. 20 Please Your Servant, O Allah.